Students’ satisfaction towards online learning systems: assessing its internal and external factors - Tan, Sharon; Chuah, Francis; Ting, Hiram (Springer, 2017)
This paper examines the internal factors (Internet self-efficacy and self-motivation) as well as an external factor (interaction) which affect university students’ level of satisfaction towards online learning systems. Field data were collected from 282 students from a public university. Data were analysed using multiple regression analysis. The outcome of the analysis suggests that these factors are significant predictors to students’ level of satisfaction when using a university’s online learning system.